Experimental study of stress anisotropy and noncoaxiality of dense sand subjected to monotonic and cyclic loading. (June 2020) - Zamanian, Mostafa; Jafarzadeh, Fardin
Abstract: The noncoaxiality of the principal stress direction and plastic principal strain increment has been broadly recognized as an influencing parameter for design of soil structures. Here we performed a series of systematic hollow cylinder experiments to study the effects of stress anisotropy on the noncoaxiality of dense Babolsar and Toyoura sands. A total of 25 undrained torsional shear tests were carried out under constant mean confining pressure, and fixed principal stress directions, α . We investigated the stress-strain behavior of dense sands for different α -directions, and cyclic stress ratio, CSR, under monotonic and cyclic loading conditions. The results show that the noncoaxiality value depends on the CSR, the level of plastic strain, and α -direction. Independent of the principal stress direction, maximum noncoaxiality value was observed at peak shear strength when there is most interlock between sand particles. Minimum noncoaxiality was recorded in α  = 45° tests, in which the direction of maximum shear stress coincided with the horizontal bedding plane direction (weakest plane).